Pengelolaan Modal Kerja dalam Peningkatan Kinerja Usaha UMKM di Desa Tebat Giri Indah, Provinsi Sumatera Selatan - Saggaff, Taufik; Yunisvita, Yunisvita; Karim, Suhartini (LPkM Universitas Bakrie, 2022)
Service to the community Service aims to help how to manage working capital efficiently and calculate working capital requirements for Micro, Small and Medium Enterprises (MSMEs) in the village of Tebat Giri Indah, North Pagaralam District, Pagaralam City, South Sumatra so that business performance (income) of MSMEs can be improved. The number of selected target audiences is 30 entrepreneurs. The implementation methods used are lecture, tutorial and question and answer. Based on the results of interviews and financial analysis, it is shown that these MSMEs always provide long terms of credit, purchases of fertilizers and pesticides in cash and often use working capital to buy consumer goods. This condition causes inefficiency in working capital management which in turn has an impact on decreasing business performance. After the counseling and assistance is carried out, these entrepreneurs of MSMEs understand how to manage working capital efficiently and calculate working capital requirements so that it is expected to improve the business performance of these MSMEs in the future.